Adaptation of a mouse Doppler echocardiograph system for assessing cardiac function and thermal performance in a juvenile salmonid. Issue 1 (3rd September 2021) - Muir, Carlie A; Neff, Bryan D; Damjanovski, Sashko
Abstract : Small rodent pulse-wave Doppler echocardiograph systems can be adapted for use in juvenile salmonids to measure metrics of cardiac function relevant to thermal performance, including maximum heart rate, ventricular filling volume, Arrhenius breakpoint temperature and arrhythmia temperature. Abstract: Measures of cardiac performance are pertinent to the study of thermal physiology and exercise in teleosts, particularly as they pertain to migration success. Increased heart rate, stroke volume and cardiac output have previously been linked to improved swimming performance and increased upper thermal tolerance in anadromous salmonids. To assess thermal performance in fishes, it has become commonplace to measure the response of maximum heart rate to warming using electrocardiograms. However, electrocardiograms do not provide insight into the hemodynamic characteristics of heart function that can impact whole-animal performance. Doppler echocardiography is a popular tool used to examine live animal processes, including real-time cardiac function. This method allows for nonsurgical measurements of blood flow velocity through the heart and has been used to detect abnormalities in cardiovascular function, particularly in mammals. Here, we show how a mouse Doppler echocardiograph system can be adapted for use in a juvenile salmonid over a range of temperatures and timeframes. Using this compact, noninvasive system, we measured maximum heart rate, atrioventricular (AV) blood flow velocity, the early flow-atrial flow ratio and stroke distance in juvenile Atlantic salmon ( Salmo salar ) during acute warming. Using histologically determined measures of AV valve area, we show how stroke distance measurements obtained with this system can be used to calculate ventricular inflow volume and approximate cardiac output. Further, we show how this Doppler system can be used to determine cardiorespiratory thresholds for thermal performance, which are increasingly being used to predict the consequences that warming water temperatures will have on migratory fishes.